Numerical study of precast segmental column under blast loads - Li, J.; Hao, Hong; Wu, C. (Pergamon, 2017)
Constructions with precast technology have seen a fast development over the past several decades. Despite advantages including short construction period, better quality control, less environmental and traffic impact, a lack of study on their behaviour under dynamic loads have prevented the widespread use of precast constructions in high seismic zones and where terrorist attack could be a concern. Among all precast structural components, precast segmental columns have been found one of the construction techniques with great potentials. Intensive research efforts have been spent on investigating the segmental columns under seismic loadings in recent years. During its service life, besides seismic action, structure may subject to other dynamic loads like impact and blast. It is therefore important to perform multi-hazard analyse to better understand structural performance. This study investigates the blast loading resistance capacities of segmental reinforced concrete (RC) columns. RC segmental columns with or without shear keys and energy dissipation bars are considered. Influence of the number of segments and different levels of post tensioning forces on column dynamic performance is also investigated. Commercial code LS-DYNA is used to perform numerical simulations of the segmental columns under different blast loadings. Accuracy of the numerical model is verified against available testing data on RC columns. Numerical results of the segmental columns under different blast loadings are calculated and compared with those of the monolithic RC columns. Discussions on the capabilities of segmental RC columns in resisting blasting loads are made with respect to those of the monolithic RC columns.